1985
DOI: 10.1111/j.1944-9720.1985.tb01805.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Playback of the Second Language: A Descriptive Study

Abstract: Spontaneous playback refers to involuntary, sometimes insistent **replay" in the mind of the second language being acquired. Anecdotal data led Krashen to hypothesize that thisphenomenon is a result of stimulation of the language acquisition device. The present study surveyed 160 foreign and second language students to enlarge the data base. It was found that spontaneous playback is widespread. The data were consistent with Krashen ' s hypothesis and with the Monitor theory; therefore, it isconcluded that thep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…proposed that involuntary mental rehearsal, termed the "Din in the Head," in second language (L2) acquirers as described by Barber (1980) is caused by stimulation of the Language Acquisition Device (LAD) and is therefore an indication that acquisition is taking place.' Bedford (1985), Parr, and Krashen (1986) and de Guerrero (1987) confirmed that the Din was widespread among L 2 learners, particularly after activities involving L2 listening. Bedford found, however, that the Din did not seem to b e as common after L2 reading.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…proposed that involuntary mental rehearsal, termed the "Din in the Head," in second language (L2) acquirers as described by Barber (1980) is caused by stimulation of the Language Acquisition Device (LAD) and is therefore an indication that acquisition is taking place.' Bedford (1985), Parr, and Krashen (1986) and de Guerrero (1987) confirmed that the Din was widespread among L 2 learners, particularly after activities involving L2 listening. Bedford found, however, that the Din did not seem to b e as common after L2 reading.…”
Section: Introductionmentioning
confidence: 88%
“…with" (2930). Bedford (1985) later described this experience with second languages as a "noticeable din or jumble ... of words, phrases, or even characteristic melody patterns" that "pop into the head at nearly any time or place" and are "quite involuntary" (286). Along with Parr and Krashen (1986) and de Guerrero (1987), Bedford found that the Din is widespread among second and foreign language students.…”
Section: Foreign Language a N N A L S -F A 1995mentioning
confidence: 99%
“…I noted that the Din experience correlates with less reluctance to speak the language, but I did not make any hypothesis about a sudden “critical stage” that leads to a “sudden and massive restructuring,” as de Bot claimed (p. 173). de Bot stated that there is no research providing evidence for his interpretation of the Din. There certainly is published research confirming that the predictions made in Krashen (1983) are correct: Bedford (1985), de Guerrero (1987), McQuillan (1996), McQuillan and Rodrigo (1995), Parr and Krashen (1986), and Sevilla (1996).…”
mentioning
confidence: 85%
“…Krashen (1983) hypothesized that "the Din is a result of stimulation of the Language Acquisition Device" (p. 43), that it is triggered by comprehensible input of the i + 1 variety, and that it will not occur in very advanced learners "since they will receive less input containing i + 1, having acquired most of the language"" (p. 43). Bedford (1985) was the first to test Krashen's Din Hypothesis empirically (see Table 1 for a summary of empirical studies). On the basis of survey data provided by 160 L2 college and FL adult learners, Bedford was able to confirm that "spontaneous playback of the second language," as he called the Din, was a widespread phenomenon rather than a process restricted to a few individuals.…”
Section: Review Of Studies On L2 Inner Speech As Mental Rehearsalmentioning
confidence: 99%
“…In 1987, Rohrer argued that inner speech is "the language of the mind" (p. 92), used in various mental operations, one of which is rehearsal. In 1990, Murphey published an article reviewing the studies conducted on the "din in the head" (Bedford, 1985;Guerrero, 1987;Krashen, 1983;Parr & Krashen, 1986) and linking this phenomenon to Vygotsky's concept of inner speech: "What [Vygotsky] calls inner speech may have a strong connection to what is now being called the Din" (Murphey, 1990, p. 55). In a few words, then, the relationship between inner speech and mental rehearsal appears to be one in which inner speech is a broad language function covering a wide range of mental operations, among which is rehearsal, the covert practice of language that is common in L2 learning. In order to empirically investigate inner speech in the L2, I conducted a study (Guerrero 1990(Guerrero /1991(Guerrero , 1994) on the nature of inner speech during mental rehearsal of the L2 as it occurred across three proficiency levels (low, intermediate, and high) of ESL college learners.…”
mentioning
confidence: 99%